Influence of cholestasis on absorption of ursodeoxycholic acid - Sauer, Peter; Petersen-Benz, Christine; Rudolph, Gerda; Klöters-Plachky, Petra; Stremmel, Wolfgang; Stiehl, Adolf (Digestive diseases and sciences, 1999)
Ursodeoxycholic acid (UDCA) has beneficialeffects in cholestatic liver diseases. Absorption ofUDCA is slow and incomplete. In the present study theeffect of cholestasis on absorption was evaluated in 10 patients with pancreatic carcinoma andextrahepatic biliary drainage.
Gesehen am 01.06.2021